Biopolymer-Based Nanoparticles: Advances in Fabrication, Characterization, and Biomedical Applications - Adebayo Samuel (International Journal of Photochemistry and Photochemical Research, 2025)
The emergence of biopolymer-based nanoparticles, particularly those composed of proteins and polysaccharides, has significantly transformed the landscape of biocompatible and biodegradable materials. These nanoparticles offer immense potential due to their ability to facilitate encapsulation and targeted delivery of bioactive compounds, enhancing therapeutic efficacy while minimizing side effects. This review explores the various fabrication techniques, including emulsification, desolvation, coacervation, and electrospray drying, emphasizing their advantages and limitations. The characterization of nanoparticles based on critical parameters such as size, surface charge, morphology, stability, and controlled release properties is discussed in detail, along with advanced analytical techniques for measurement. Furthermore, this article delves into the diverse biomedical applications of these nanoparticles, including drug delivery, wound healing, tissue engineering, and vaccine development. The review also highlights current challenges and future perspectives, focusing on scalability, regulatory considerations, and novel formulations that integrate multiple functionalities for enhanced performance. With ongoing advancements in nanotechnology and material science, biopolymer-based nanoparticles continue to be a promising avenue for various biomedical applications, fostering innovation in targeted therapies and regenerative medicine.
Keywords: Biopolymers; Controlled release; Encapsulation; Nanoparticles; biomedical applications